2022
DOI: 10.1186/s10020-022-00490-9
|View full text |Cite
|
Sign up to set email alerts
|

BNIP3 mediates the different adaptive responses of fibroblast-like synovial cells to hypoxia in patients with osteoarthritis and rheumatoid arthritis

Abstract: Background Hypoxia is one of the important characteristics of synovial microenvironment in rheumatoid arthritis (RA), and plays an important role in synovial hyperplasia. In terms of cell survival, fibroblast-like synovial cells (FLSs) are relatively affected by hypoxia. In contrast, fibroblast-like synovial cells from patients with RA (RA-FLSs) are particularly resistant to hypoxia-induced cell death. The purpose of this study was to evaluate whether fibroblast-like synovial cells in patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 51 publications
2
8
0
Order By: Relevance
“…The well known, the receptor-mediated mitophagy can be activated by hypoxia, such as BNIP3-mediated mitophagy [31][32]. FLS maintained intracellular redox balance through BNIP3-mediated mitophagy to promote cell survival under hypoxia in RA [17]. Our results also showed that the expressions of mitophagy related proteins BNIP3 and LC3B in RA synovium were significantly increased (Fig.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…The well known, the receptor-mediated mitophagy can be activated by hypoxia, such as BNIP3-mediated mitophagy [31][32]. FLS maintained intracellular redox balance through BNIP3-mediated mitophagy to promote cell survival under hypoxia in RA [17]. Our results also showed that the expressions of mitophagy related proteins BNIP3 and LC3B in RA synovium were significantly increased (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…However, one of the major pathological features of RA is the abnormal proliferation of FLS, manifesting as hyperplasia of synovial tissue [16]. Recent research has found that FLS of RA maintained intracellular redox balance through BCL2/adenovirus e1B 19 kDa protein interacting protein 3 (BNIP3)-mediated mitochondrial autophagy (mitophagy) to promote cell survival under hypoxia [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To generate conditioned medium, we cultured STRO3 + enriched MSCs for 24 h at either atmospheric oxygen tension, or 2% O 2 to simulate the hypoxic environment of the intervertebral disc. MSCs cultured in hypoxia exhibited reduced survival time, as evidenced by reduced numbers of CD90 + cells ( Figure 4C ) and enhanced expression of BNIP3, a marker of cell death induced by hypoxia ( Zhang and Ney, 2009 ; Deng et al, 2022 ), after 48 h ( Figure 4D ). To limit the confounding effects of cell death in hypoxia, MSCs were cultured for 24 h in either normoxic or hypoxic conditions and CM were collected for subsequent experiments.…”
Section: Resultsmentioning
confidence: 99%
“…In hypoxic environments, RA-FLS cells exhibited a more pronounced increase in the expression of HIF-1α transcriptional regulatory genes, higher BNIP3 expression, and stronger mitochondrial autophagy and proliferative activity ( 63 ).…”
Section: Altered Fls Metabolism and Intracellular Signaling Pathway T...mentioning
confidence: 99%